Evaluation of Biochemical Effects of Anelgesic Agents and Conotoxins of Mediterranean Cone (Conus mediterraneus) on Bradykinin and Histamine Causing Pain in Female Sheep (Ovis aries) - Bayazit, Vahdettin (ACADEMIC JOURNALS INC, 2011)
The purpose of this study was performed to test effects of the nanoanelgesic and nanoconotoxin materials on bradykinin and hystamine causing the various pains. Normal blood histamine values were between 5 mL ( 25 and 65 ng mL(-1)). Blood samples taken as intra venous from six month old female sheep (Ovis aries). In this study, bradykinin and histamine concentrations were selected as 65 ng mL(-1) and levels of chemical analgesic nanoagents are administered as 8 mL (40 ng mL(-1)). Conicamin, Cycloamphilectene 2, Plakohypaphorine D, Pourewic acid A, Cadlinolide C, Petrocortyne A, Petrosaspongiolide M, Petrosaspongiolides M-R, Pseudopterosin N, Seco-pseudopterosin E, Elisabethaclione, Pseudopterosin R, alpha-Conotoxin, mu-conotoxin, omega-conotoxin, Des(Gly1) contryphan R, Contryphan-R, Bromocontyphan-R, Contryphan-Sm, Contryphan-P, Contryphan-R/Tx, Contryphan-Tx, Contryphan-Vn, Leu-contryphan-P, Leu-contryphan-Tx, Glaconryphan-M mu-conotoxins GIIIA, mu-conotoxins GIIIB, mu-conotoxins GIIIC, mu-toxin mu-PIIIA, alpha-conotcodns GI, alpha-conotoxins GIA, alpha-conotoxins GII, alpha-conotoxins MI, astaxanthin, bolinaquinone, cacospongionolide B and Clathriol are decreased significantly bradykinin and hystamin levels in the blood (p<0.01) but delta-conotoxin K-conotoxin are decreased significantly more less than other agents (p<0.05).
Keywords: Pain; nanoanelgesic; nanoconotoxins; mediterranean cone (Coitus mediterraneus) bradykinin; histamine